The Allelopathic Effects of Turkish Hulled Wheat Lines on Germination of Amaranthus retroflexus L. and Lolium perenne L. Seeds - Yasin Emre KİTİŞ (Abant İzzet Baysal University, 2021)
The aim of this study was to determine allelopathic effects of some emmer (Triticum dicoccum Schrank) and einkorn (Triticum monococcum L.) wheat lines on germination of redroot pigweed (Amaranthus retroflexus L.) and perennial ryegrass (Lolium perenne L.). For this purpose, fourty-nine emmer and thirty-six einkorn wheat lines with two commercial durum wheat cultivars (cvs. Svevo and Saragolla) were sown in experimental field of Akdeniz University. Leaves of emmer and einkorn lines were cut at the end of tillering stage (Z29) to obtain sufficient plant extracts. Afterwards, germination rates of weed species were recorded by carrying out petri experiments. Many of the emmer and einkorn wheat lines highly inhibited the germination of two weed species compared to durum wheat cultivars but some lines were found very efficient for inhibition of both species. Four lines of emmer and eight lines of einkorn wheat inhibited germination of redroot pigweed over 90% while one emmer line and six lines of einkorn inhibited germination of ryegrass over 80%. According to average germination values, it was revealed that while ten lines of emmer and seventeen lines of einkorn reduced germination of both weed species by more than 50%, effect of commercial wheat cultivars remained at the rate of 35% and 18%, respectively. As a result, there was a clear evidence that some lines of emmer and einkorn wheat had a suppressive effect on germination of two important weed species. This is the first report about the allelopathic potential of the emmer and einkorn wheats. However, further researches are needed to test effectiveness of these wheats on allelopathy under both greenhouse and field conditions in detail.